Funciones desempeñadas como asesor de negocios Senior II de la Caja Municipal de Ahorro y Crédito S.A., agencia Virú - periodo 2017 - Díaz Chilón, Ángel Alfredo (2019)
The present work of professional sufficiency, has as general objective to describe the functions performed in the Municipal Savings and Credit Bank of Trujillo S.A., Virú agency - period 2017, in the position of Senior Business Advisor II. This document is structured in four chapters, which describes the institutional context of the Municipal Savings and Credit Institutions (CMACs) within the Peruvian microfinance sector, as well as the functions commissioned and performed according to the Organization and Functions Manual (MOF) of the entity. Observation and documentary analysis were used as the study methodology. In addition, the theoretical foundation was made on the problems identified in the institution, as well as the general issues regarding the financial environment in which the company operates. At the same time, a critical analysis of the functions performed within the institution was carried out. Finally, through improvement strategies, the three problems identified were solved; Limited labor relations between the area of credits and the area of operations, poor training in sales techniques and credit recovery to business advisors, and lack of incentives and recognition for the good performance of employees. Among the most outstanding conclusions, it was possible to determine that within the credit area of the Virú Agency there is a bad labor relationship, it has slow approval processes, and there is a lack of training for credit personnel in sales and collection techniques.